Estimation Of Drug Stocks In Pharmacies In The Covid-19 Era Using The Fp-Growth Algorithm - Yennimar; Johanes T. Gultom; William S. Purba; Dewi S. Sihotang (Jurnal Mantik, 2022)
In the era of covid-19, the response in controlling covid-19 requires an adequate supply of medicines in hospitals and pharmacies. The supply of these drugs is felt to be very important because seeing the impact of the covid-19 virus is very dangerous for human health. Therefore, the existence of the supply of medicines in pharmacies during this Covid era really needs to be considered. Every transaction of the sale of the drug in pharmacies is always recorded. This sales transaction data can be processed to find certain patterns in selling drugs in a certain period of having so many drug sales transaction activities. If the sales transaction data is analyzed, a pattern can be found out that is very helpful in estimating drug stocks from the drug sales data. To be able to estimate drugs, the right method is needed in order to get accurate results. One of them is the Fp-Growth method. With Fp-Growth, data is entered for calculations based on drug sales data so as to produce conclusions of minimum support and minimum confidence values. Based on this study, 35 data on drug sales transactions were taken. The test results of this study obtained calculation results from simultaneous drug sales data that are often purchased by consumers with the highest accuracy are 17.14% and 50%, namely Paracetamol and CTM.